Color Stability of Bulk-fill Resins Immersed in Chicha: In vitro Study - Diana Fele Layza-Mayo; Daría Cristina Suárez-Rojas; Consuelo Marroquín-Soto; Guillermo Cano-Verdugo (Acta Stomatologica Croatica, 2025)
Objective: To analyze the color stability of Bulk-fill resins immersed in chicha morada and light-cured at different distances (0 mm, 2 mm and 4 mm). Methods: This in vitro experimental study included a total of 216 Bulk-fill resin discs. The specimens were distributed into nine groups of 24 discs based on the type of resin (3M ESPE® Filtek™ Bulk Fill®, Ivoclar® Tetric N-Ceram Bulk Fill® and FGM® Opus Bulk-fill APS®), light-curing distances (0, 2 and 4 mm) and staining solution (control with distilled water and Naturalle® chicha morada). Color measurements were taken 24 hours after fabrication and immersion in distilled water and Naturalle® chicha morada at 24 hours, 1 weekand 3 weeks. Results: Light-curing distances affected the color stability of the resins with 3M ESPE® and Ivoclar®, thusexhibiting significant color changes at all evaluated time points when immersed in chicha morada. For the Delta (ΔE) value 3M ESPE® and Ivoclar® resin discs immersed in chicha morada showed significant changes at 24 hours 1 week and 3 weeks (p = .001, p = .000 and p = .000; and p = .000 p = .000 and p = .000 respectively). However, FGM® resin discs exhibited significant changes only at 24 hours and 1 week (p = .000 and p = .001). FGM® showed better color stability compared to 3M ESPE® and Ivoclar® at 3 weeks of immersion in chicha morada. All three commercial brands showed a significant decrease in the “L” value as immersion time in chicha morada increased. Conclusions: The study concluded that FGM® demonstrated better chromatic stability over time compared to 3M ESPE® and Ivoclar® Ceram, which exhibited significant color changes influenced by immersion duration and photopolymerization distance.